HUBUNGAN HIGIENE PETUGAS DEPOT GALON DENGAN JUMLAH BAKTERI E. COLI AIR MINUM PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DI KECAMATAN UMBULHARJO DAN KECAMATAN KOTAGEDE YOGYAKARTA - Alfian Alfian; Surahma Asti Mulasari; Ichtiarini nurullita santri (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
Along with the increase in population, the need for drinking water is increasing. Refill drinking water depots are an alternative to meet air needs. Good quality drinking water does not contain E. coli and coliform bacteria. The purpose of this study was to determine whether there was a relationship between gallon depot officers and the number of E.coli bacteria in drinking water at refill drinking water depots (DAMIU) in Umbulharjo and Kotagede districts, Yogyakarta. This study used an analytic observational method with a cross sectional research design. The total sample used is 32 with data collection techniques using a check list and research subjects are DAMIU officers. Data analysis in this study used the Fisher Exact Test. The results showed that the hygiene of DAMIU officers obtained 9 respondents (28.1%) had poor hygiene conditions, while 23 respondents (71.9%) had good hygiene conditions. The results of the statistical test obtained a p-value of 0.314, which means that there is no relationship between the hygiene of DAMIU officers and the number of E. coli bacteria in Umbulharjo District and Kotagede District, Yogyakarta in 2018. So people with poor hygiene do not necessarily increase the risk of the presence of E. coli bacteria. in drinking water as much as 0.391 times greater than people who have good sanitation hygiene. The conclusion of this research is that no correlation between the hygiene of gallon depot officers and the number of E. coli bacteria in refilled drinking water in Umbulharjo and Kotagede districts of Yogyakarta (p-value 0.314; RP=0.391; CI=0.096 – 1.591).